Primary productivity estimation in relation to trophic status in Altadighi in Naogaon District, Bangladesh - Hossain, M Abul; Mannan, MA; Hossain, M Altaf (University Journal of Zoology, Rajshahi University, 2007)
Key words: Primary productivity; trophic status; Altadighi Univ. j. zool. Rajshahi Univ. Vol.22, 2003. pp. 41-45